2009
DOI: 10.1111/j.1834-7819.2008.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Abfraction: separating fact from fiction

Abstract: Non-carious cervical lesions involve loss of hard tissue and, in some instances, restorative material at the cervical third of the crown and subjacent root surface, through processes unrelated to caries. These non-carious processes may include abrasion, corrosion and possibly abfraction, acting alone or in combination. Abfraction is thought to take place when excessive cyclic, non-axial tooth loading leads to cusp flexure and stress concentration in the vulnerable cervical region of teeth. Such stress is then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
114
0
54

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(175 citation statements)
references
References 45 publications
1
114
0
54
Order By: Relevance
“…37 Similarly, consideration should perhaps be given to using RMGI more frequently in the restoration of NCCLs, as other studies have also shown high retention rates in comparison to other materials. 38,39 Occlusal factors are considered by many to be important in the aetiology of NCCLs [40][41][42] and in the success of restorations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Similarly, consideration should perhaps be given to using RMGI more frequently in the restoration of NCCLs, as other studies have also shown high retention rates in comparison to other materials. 38,39 Occlusal factors are considered by many to be important in the aetiology of NCCLs [40][41][42] and in the success of restorations.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 This study, however, did not identify any statistically significant effect of any of the occlusal factors recorded on time to failure, which supports the findings of those who discount the influence of occlusal loading as anything more than a co-initiating factor. 37,56 No evidence of an association between the elastic modulus of a restorative material and time to failure was found, as there was no difference observed between the Kaplan-Meier plots of either of the two composite types and compomer, while glass ionomer, the material with the lowest modulus of elasticity, recorded the greatest proportion of failures. The issue of elastic modulus is somewhat complicated as materials within one classification may have quite distinct mechanical properties and so it cannot necessarily be assumed, for example, that all composites have a significantly higher elastic modulus than all RMGIs.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, in this study there was no evidence to support early failure of restorations being significantly associated with any of the occlusal features recorded, which lends further support to recent reviews which question the role of occlusion in the development of non-carious cervical lesions (NCCLs). 20,21 In the univariate analysis, contamination with moisture and level of oral hygiene did not appear to increase two-year failure; however the general level of moisture contamination was minor and only 10% of patients displayed poor oral hygiene. Although no significant association with moisture contamination was identified using univariate analysis, the multivariable analysis suggested that moisture contamination increased the chance of early failure, after adjusting for other important factors.…”
Section: Multi-variable Logistic Regressionmentioning
confidence: 92%
“…Clinical studies have shown that they are associated with bruxism, wear facets, and premature contacts but no investigations have been able to confirm any causal relationship 15,30 .…”
Section: --Occlusal Trauma As An Etiological Factormentioning
confidence: 99%
“…In conclusion, it is no longer deemed advisable to use selective grinding in an attempt to cure abfraction lesions 30,36 . Nevertheless, in the framework of orthodontic treatment, it may be worthwhile for orthodontists to discern specific areas of interference and to modify the values of lateral torque during finishing stages of treatment.…”
Section: --Occlusal Trauma As An Etiological Factormentioning
confidence: 99%